Photoperiodic Response of Growth of Pinus caribaea Seedlings: I Effect on Stem Height and Diameter and Tracheid Characters - Bhatnagar, H. P.; Talwar, K. K. (Indian Forester, 1978)
Pot culture experiment was conducted with the seedlings of Pinus Caribaea to evaluate the effect of different photoperiodic treatments on growth and tracheid characters. The study haa revealed that both growth and tracheid characters are responsive to day length variations. The results indicate significant variations in stem height and diameter and tracheid characters. Long day treatment has significantly increased stem height, tracheid length, tracheid diameter and tracheid lumen diameter. Significant increase in stem diameter has been observed under interrupted day treatment.